Herta Müller - Brigid Haines (University of Wales Press, 1998)
The first book in English to be devoted exclusively to Herta Müller, this collection of essays is intended both as an introduction for the general reader and a resource for the specialist. It contains ten previously unpublished short texts by Müller, together with a revealing interview and a biographical outline. Six essays by British and German academics interpret key texts in detail and assess vital aspects of Müller's entire oeuvre. The essays are complemented by the fullest bibliography on Müller published since 1991.